2010
DOI: 10.1123/rsj.34.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction for Campus Recreation Professionals within NIRSA Institutions

Abstract: An international investigation was conducted to determine the overall job satisfaction of college campus recreation employees who are members of the National Intramural Recreational Sports Association (NIRSA). Demographic information was gathered to provide statistical analysis based on (a) region; (b) size of school; (c) private versus public; (d) four-year versus two-year schools; (e) rural, suburban, and urban location; (f) years in the profession; and (g) reporting structure. The following work related are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
(13 reference statements)
3
14
0
Order By: Relevance
“…In the current study, increased opportunity for promotion/advancement improved the level of job satisfaction. Two previous studies of job satisfaction in campus recreational sports had similar findings in terms of years of experience leading to high levels of job satisfaction (Stier et al, 2010;Zhang et al, 2003). Furthermore this finding supported the notion that the length of service is a good predictor of job satisfaction (Sarket, Crossman, & Chinmeteepituck, 2003).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the current study, increased opportunity for promotion/advancement improved the level of job satisfaction. Two previous studies of job satisfaction in campus recreational sports had similar findings in terms of years of experience leading to high levels of job satisfaction (Stier et al, 2010;Zhang et al, 2003). Furthermore this finding supported the notion that the length of service is a good predictor of job satisfaction (Sarket, Crossman, & Chinmeteepituck, 2003).…”
Section: Discussionsupporting
confidence: 66%
“…Since the turn of the 21 st century, only four studies focused upon campus recreation can be found in the literature, and virtually nothing on job satisfaction was studied or reported prior to 2000. The focus of study in this setting has included overall job satisfaction of all employees (Stier, Schneider, Kampf, & Gaskins, 2010), the job satisfaction of administrators at four-year institutions (Kaltenbaugh, 2008(Kaltenbaugh, , 2009Zhang, DeMichele, & Connaughton, 2004), and the satisfaction of top administrators with reporting structure (Schneider, Stier, Kampf, Haines & Wilding, 2005). The research dimension missing from the campus recreational sport literature is a focus upon personal correlates relating to job satisfaction which may help to not only illustrate a different perspective of job satisfaction, but also take into account differences between people (Oshagbemi, 2003).…”
Section: Salarymentioning
confidence: 99%
“…Several studies have been conducted to assess job satisfaction among campus recreation administrators. Stier, Schneider, Kampf, and Gaskins (2010) Findings indicated that 93% of campus recreation administrators were satisfied with their job;…”
Section: Conscientiousnessmentioning
confidence: 99%
“…Research assessing job satisfaction and work environment on college campuses has been performed. Studies examining college and university presidents (Perrakis, Galloway, Hayes, & Robinson-Galdo, 2011), faculty members (Bozeman & Gaugahan, 2011;Marston & Brunetti, 2009) and campus recreation professionals (Kaltenbaugh, 2009;Stier, Schneider, Kampf, & Gaskins, 2010) suggest that work environment may play a role in the participants' overall satisfaction.…”
Section: Purpose Of the Studymentioning
confidence: 99%